Exploring Attachment and Internal Representations in Looked-After Children - Hillman, Saul; Cross, Richard; Anderson, Katharine (Frontiers in Psychology, 2020)
Background: this article explores the Story Stem Assessment Profile (SSAP), a narrative-based measure, for the assessment of internal representations in children between the ages of 4 and 11 years old. Methods: the findings draw upon two samples of children comprising of a sample of looked-after children (LAC) (n=42) and a community-based population (n=42). Results: using the SSAP, the finding indicate the instrument’s discriminant validity with strong differences being displayed between the two populations. Consistently, children in the LAC sample displayed more disorganized, avoidant and negative representations, whilst at the same time having significantly fewer representations characteristic of ‘secure’ attachment. Conclusions: Further findings are reported on the individual themes and codes that fell within these four constructs. These findings are discussed, and limitations and implications of study are presented.